Aplicação de enonas cíclicas como precursores para síntese de trifluoracetiltetraidropiridinas e 1H-pirazóis-3(5)-carboxilato de etila - Fernandes, Liana da Silva (2010)
The present work describes the synthesis of novel 1-alkyl(aryl)-2-alkoxy-5-trifluoroacetyl-1,2,3,4-tetrahydropyridines, aza-condensed tetrahydropyridines and ethyl-1H-pyrazoles-3(5)-carboxylate from the use of cyclic enones as precursors. The 1-alkyl(aryl)-2-alkoxy-5-trifluoroacetyl-1,2,3,4-tetrahydropyridines were synthesized using stoichiometric amounts of trifluoroacetyl dihydropyranes and different primary amines in 55 96% yield, under basic catalysis, whereas the aza-condensed tetrahydropyridines were synthesized using stoichiometric amounts of trifluoroacetyl dihydropyranes and different diamines, leading to the desired products in 81 96% yield. The acylation of 2,3-dihydrofuran, 3,4-dihydropyran and 2-alkoxy-3,4-dihydro-2H-pyran with ethyloxallyl chloride furnished esterified enones (4-(2-ethyl-oxoacetate)2,3-dihydrofuran, 5-(2-ethyl-oxoacetate)-3,4-dihydro-2H-pyran and 2-methoxy-5-(2-ethyl-oxoacetate)-3,4-dihydro-2H-pyran) in 47 81% yield. Finally, the cyclocondensation reaction between enones (4-(2-ethyl-oxoacetate)-2,3-dihydrofuran-2-oxoacetate, 5-(2-ethyl-oxoacetate)-3,4-dihydro-2H-pyran) with different hydrazines led to the synthesis of 1H-pyrazole-3(5)-carboxylate ethyl ester in 62 96% yield. The N1 H substituted ethyl-1H-pyrazole-3(5)-carboxylate esters were N-alkylated with alkyl , allyl , and benzyl halides leading to the desired N-substituted pyrazoles in 48 96% yield.